University Transfer Programs in the Community College - Dennison, John D. (Canadian Journal of Higher Education, 1978)
During recent years, the increasing public demand for community college programs which lead to immediate employment has created something of an "identity crisis "for college faculty in British Columbia. Orginally, the college concept in this province reflected a comprehensive curriculum with a major emphasis upon academic programs which provide the student with transfer credit to the universities. However, comment in the public press and statements from the Ministry of Education indicate that the academic programs are very much out of favor and perhaps should be relegated to the universities. In view of the uncertainty which this situation has produced, it seemed important to take a new look at the college academic - transfer programs in 1977. The study which followed produced several important facts. Despite rumour to the contrary, enrollment in college academic programs has not declined over the past five years, but has remained at approximately 65%. The percentage of university transfer students actually transferring from colleges to universities has reached 16%, although there is considerable variation among the individual colleges. Studies indicate that only about half of the university transfer students actually " i n t e n d " to transfer to university. Obviously, many students in the university transfer programs are interested in general education or merely exploring their capacity or interest in academic study. At the University of British Columbia, the percentage of under- graduate students who have transferred from colleges has grown from 9% in 1969 to 18% in 1976. The majority of these students are successful in obtaining a university degree. Finally, it should be stated that the term "university transfer" is really a misnomer. The values of an academic education are just as real as ever, and transfer to university is not the sole criterion on which these programs should be judged. The academic programs of the community college meet the needs of a clientele served by no other institution, offer educational opportunity for a segment of society which has been ignored in the past and provide a major impact upon the quality of life in its immediate community.